The popular economic proposal of the «Asociación Circuito Ecoturístico Lomas de Lúcumo» - García Castillo, Alicia (2019)
The present study aims to answer if the development of the community tourism experience of the «Asociación Circuito Ecoturístico Lomas de Lúcumo» (ACELL) of the Rural Quebrada Verde Rural Center is based on the development of a dynamic of popular social relations. In order to do this, an approach is dedicated to the recovery of the memory of the experience of the association, the analysis of its internal organization, the relationships that relate to actors and agents of its surroundings, and, the scenarios to the future. Through indepth interviews and diverse local environments sought to investigate and unveil the dynamics developed within the ACELL. It was possible to see that the ACELL deployed actions aimed at the conservation of the lomer ecosystem, as well as the satisfaction of a part of the population’s primary needs, the subsistence under the community redistributive ecotourism that is the experience of ACELL in Paths of a popular economy.